2001
DOI: 10.1079/bjn2001469
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in African women in the North West Province, South Africa is associated with an increased risk of non-communicable diseases: the THUSA study

Abstract: The objective of the present study was to assess the relationship between anthropometric measurements and risk factors for non-communicable diseases (NCD) in South African black women. A cross-sectional sample of 1040 apparently healthy black female volunteers, 15 -70 years old, was recruited from thirty-seven randomly selected sites in the North West Province, stratified according to level of urbanisation. We analysed the association between BMI, waist:hip (WHR), waist circumference (WC) and skinfold measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
43
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 29 publications
10
43
0
Order By: Relevance
“…The proposed mechanism for established MS could be that visceral adiposity is associated with impaired glucose tolerance and atherogenic dyslipidaemia, which is a combination of increased triglyceride and reduced HDL levels as well as LDL particles 13,15. As intra-abdominal fat is highly lipolytic and increases fatty acid transport to the liver, a decrease in insulin clearance is inevitable, causing hyperinsulinaemia 17.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed mechanism for established MS could be that visceral adiposity is associated with impaired glucose tolerance and atherogenic dyslipidaemia, which is a combination of increased triglyceride and reduced HDL levels as well as LDL particles 13,15. As intra-abdominal fat is highly lipolytic and increases fatty acid transport to the liver, a decrease in insulin clearance is inevitable, causing hyperinsulinaemia 17.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both visceral obesity and hyperinsulinaemia are associated with increased sympathetic activity, favouring re-absorption of Na + 17. Increased circulating Na+ causes vasoconstriction, and hypertension follows 15,17…”
Section: Discussionmentioning
confidence: 99%
“…In the THUSA study, a cross-sectional study on the black population of the North West Province of South Africa, obesity was the most important factor associated with elevated total serum cholesterol and low-density lipoprotein cholesterol concentrations during urbanisation (28) . In addition, among the women in the THUSA study a high rate of obesity was reported that was associated with an increased risk for non-communicable disease (29) . The large number of South African metropolitan adults (21 %; 2Á2 million) who consider the influence of eating certain food types on weight loss as unimportant is of concern.…”
Section: Discussionmentioning
confidence: 99%
“…2 Furthermore, the country is experiencing a nutrition transition 6,7 that features diet-related conversions and a reduction in physical activity patterns 8 that are exceptionally evident in black South African women who are in the midst of an urbanisation phase. 3,9,10 A previous countrywide survey, in which HIV status was unknown, revealed that 32% of black women were obese and 26.7% were overweight, 11 while 53.8% were overweight or obese in a study in North West province (that borders the Free State). 4 However, participating in some form of physical activity would have a favourable eff ect on cardiovascular health, while combating outcomes such as type 2 diabetes, 12 respiratory infections 13,14 and overweight or obesity.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] In 2010, the HIV prevalence rate in women attending antenatal clinics in the Free State province was established to be an alarming 30.6%. 2 Furthermore, the country is experiencing a nutrition transition 6,7 that features diet-related conversions and a reduction in physical activity patterns 8 that are exceptionally evident in black South African women who are in the midst of an urbanisation phase.…”
Section: Introductionmentioning
confidence: 99%